Innovation in Online Birth Certificate Services: A Qualitative Study of Population Administration Reform at the Department of Population and Civil Registration of Wajo Regency - Aris, Muhammad; Sumarno, Sumarno (Pattimura University, 2026)
This study examines innovation in online birth certificate services as part of population administration reform implemented by the Department of Population and Civil Registration of Wajo Regency, Indonesia. The research aims to analyze the form of service innovation, its implementation process, and the supporting and inhibiting factors influencing its effectiveness. This study employs a qualitative descriptive approach, with data collected through observation, in-depth interviews, and documentation. Informants include key officials, service operators, and community members who utilize online birth certificate services. The analysis is guided by Rogers’ innovation attributes framework, which includes relative advantage, compatibility, complexity, trialability, and observability. The findings reveal that online birth certificate services provide significant benefits in terms of efficiency, accessibility, transparency, and time effectiveness compared to conventional services. The innovation enables citizens to submit applications remotely, reduces administrative costs, and minimizes face-to-face interactions. However, several challenges remain. Supporting factors include strong government commitment, leadership support, adequate regulatory frameworks, inter-agency collaboration, and improving digital infrastructure. Conversely, inhibiting factors consist of limited public awareness, low digital literacy among some community members, insufficient human resources, budget constraints, and uneven internet connectivity. Cultural habits and limited socialization efforts also affect the adoption of online services. Overall, the study concludes that online birth certificate service innovation has positively contributed to improving public service quality, although its sustainability depends on continuous capacity building, infrastructure enhancement, and intensive public outreach. The findings provide practical implications for local governments seeking to strengthen digital-based public service delivery in population administration.